A Review of Probiotics Role in Enhancing Sperm Quality - Andrian Fahmi Bahar (Journal of Global Pharma Technology, 2016)
Introduction: Probiotics have been used widely in medical world, but its use in infertility, especially in male infertility, is yet still unbeknown. The aim of this paper is to review the usefulness of probiotics in enhancing sperm quality in order to treat male infertility. Methods: Narrative review on literature surfing in the Pub med database, as well as key words, that is probiotic, Lactobacillus, sperm quality, male infertility, sperm motility, sperm concentration, sperm morphology, sperm DNA fragmentation. Results: The results on literature surfing are mainly yielding to the positive effect of probiotics in enhancing sperm quality in animals, and in human, although there are some literature that shows conversely. The production of Gamma-Amino Butyric Acid and antioxidants by the probiotics are thought to be the main mechanism for the improvement of the sperm quality, especially in the enhancement of the sperm concentration, motility and the decrease of the DNA fragmentation. Contrarily, negative results left another mystery for researchers to solve. Conclusions: Although the probable mechanisms of probiotics role in enhancing sperm quality have been unveiled, still more researches should be performed to find more evidence in this issue.Keywords: Probiotic, Sperm quality, Sperm motility, Sperm concentration.